Conservação pós-colheita de mangaba (Hancornia Speciosa Gomes) - Nasser, Flávia Aparecida de Carvalho Mariano [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study aimed to evaluate the best conditions for postharvest fruit mangaba. The experiments were conducted in the laboratory of Food Technology of the University Estadual Paulista (UNESP) Campus Ilha Solteira. In the first experiment, the mangabas in three maturity stages were packed in polyethylene terephthalate, polystyrene trays covered with polyvinyl chloride film and plastic bag with closure. The treatments consisted of combinations between the degrees of maturation and packaging and were evaluated: loss of weight, firmness, vitamin C, pH, soluble solids, titratable acidity, maturation index, reducing sugars, polyphenoloxidase activity, peroxidase activity, chlorophyll and visual appearance. The best preservation was once the fruits packed in Styrofoam tray, keeping great rankings throughout the storage period. In the second experiment, mangabas the stadium in time were placed in polystyrene trays covered with polyvinyl chloride film. They received treatment with different chitosan concentrations (0, 0.25, 0.5, 1 and 2 %). Evaluations were loss of weight, firmness, vitamin C, soluble solids, titratable acidity, maturation index, pH, reducing sugar and visual appearance. Treatments with chitosan in concentrations of 1% and 2% were shown to be effective with maximal notes to the final storage. In the third experiment, mangabas the stadium in time were placed in polystyrene trays covered with polyvinyl chloride film. Then, received treatments to absorb ethylene using different concentrations of potassium permanganate (0, 1, 2 and 3%). Evaluations were weight loss, firmness, vitamin C, soluble solids, titratable acidity, maturation index, pH, reducing sugar and visual appearance. Sachets containing 1 and 2 grams of potassium permanganate provides better visual appearance mangabas of time. In the fourth experiment fruits mangaba receiving mild osmotic dehydration for 10 minutes was selected. Then taken to a dryer with forced hot ...

Objetivou-se avaliar as melhores condições pós-colheita para frutos de mangaba. Os experimentos foram conduzidos no laboratório de Tecnologia de Alimentos da Universidade Estadual Paulista (UNESP) Campus de Ilha Solteira. No primeiro experimento, as mangabas nos três estádios de maturação foram acondicionadas em polietileno tereftalato, bandeja de Poliestireno expandido recoberto com filme de policloreto de vinila e saco plástico com fechamento. Os tratamentos foram constituídos das combinações entre os graus de maturação e embalagens e foram avaliadas: perda de massa fresca, firmeza, vitamina C, pH, sólidos solúveis, acidez titulável, índice de maturação, açúcares redutores e aparência visual. A melhor conservação foi nos frutos de vez acondicionados em bandeja de isopor, mantendo classificação ótima em todo período de armazenamento. No segundo experimento, mangabas no estádio de vez foram acondicionadas em bandejas de poliestireno expandido recobertas com filme de policloreto de vinila. Receberam os tratamentos com diferentes concentrações de quitosana (0; 0,25; 0,5; 1 e 2%). As avaliações realizadas foram: perda de massa fresca, firmeza, vitamina C, sólidos solúveis, acidez titulável, índice de maturação, pH, açúcar redutor e aparência visual. Os tratamentos com quitosana nas concentrações de 1% e 2% mostraram-se efetivos com notas máximas até o final do armazenamento. No terceiro experimento, mangabas no estádio de vez foram acondicionadas em bandeja de poliestireno expandido recobertas com filme de policloreto de vinila. Em seguida, receberam os tratamentos para absorver etileno utilizando diferentes concentrações de permanganato de potássio (0; 1; 2 e 3%). As avaliações realizadas foram: perda de massa, firmeza, vitamina C, sólidos solúveis, acidez titulável, índice de maturação, pH, açúcar redutor e aparência visual. Os sachês contendo 1 e 2 gramas de permanganato de potássio ...
Keywords: Mangaba - Conservação; Mangaba - Tecnologia pós colheita; Mangaba - Armazenamento; Mangaba - Embalagens; Food Postharvest technology